2017
DOI: 10.3390/su9112148
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Contracts in a Dual-Channel Supply Chain with a Risk-Averse Retailer

Abstract: Dual channels have become popular strategies for manufacturers due to the development of innovative selling platforms. Examples in practice also show that the lack of relationship management, such as cooperation and sharing, may cause an unsustainable supply chain performance. However, previous studies on coordination of dual-channel supply chains always focus on the contribution to profits and neglect the sustainability of relationship development between channel members. In this paper, we study the coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…In addition, they adopted the contract to coordinate a mixed-channel supply chain which consisted of several homogeneous retailers and direct selling channels. Zhu et al [33] studied the order decision making of members in a dual-channel supply chain with a risk-neutral manufacturer and a risk-averse retailer, designed a risksharing contract which is a hybrid with multiple contracts, and found that the risk-sharing contract could perform steadily when the market circumstance varies. He et al [24] studied a single-retailer single-vendor dual-channel supply chain model in which the vendor sells deteriorating products through its direct online channel and the indirect retail channel and developed a revenue sharing and two-part tariff contract to coordinate the supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, they adopted the contract to coordinate a mixed-channel supply chain which consisted of several homogeneous retailers and direct selling channels. Zhu et al [33] studied the order decision making of members in a dual-channel supply chain with a risk-neutral manufacturer and a risk-averse retailer, designed a risksharing contract which is a hybrid with multiple contracts, and found that the risk-sharing contract could perform steadily when the market circumstance varies. He et al [24] studied a single-retailer single-vendor dual-channel supply chain model in which the vendor sells deteriorating products through its direct online channel and the indirect retail channel and developed a revenue sharing and two-part tariff contract to coordinate the supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The need for effective operations is the goal of many supply chain stakeholders in order to survive in a competitive environment. Nowadays, supply chain stakeholders put more emphasis on customer satisfaction and timely product deliveries [8][9][10][11][12]. According to Dong et al [10], many companies started investing substantial monetary resources into sustainability projects, aiming to reduce emissions during the manufacturing process, meet customer expectations, as well as improve social and environmental sustainability of supply chain operations.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the project value, a reasonable cash-flow model that reflects the profitability impact factors that are the input variables of the DCF method should be established. This paper defines the following 15 profitability impact factors, (1) capital expenditure; (2) material cost; (3) labor cost; (4) net working capital; (5) overhead cost; (6) sale price; (7) production; (8) exchange rate; (9) corporate tax rate; (10) debt-to-equity ratio; (11) risk-free interest rate; (12) market risk premium; (13) beta; (14) cost of debt (COD) before tax; and (15) …”
Section: Traditional Decision-making Process For the Dcf Modelmentioning
confidence: 99%
“…To assess the project value, a reasonable cash-flow model that reflects the profitability impact factors that are the input variables of the DCF method should be established. This paper defines the following 15 profitability impact factors, (1) capital expenditure; (2) material cost; (3) labor cost; (4) net working capital; (5) overhead cost; (6) sale price; (7) production; (8) exchange rate; (9) corporate tax rate; (10) debt-to-equity ratio; (11) risk-free interest rate; (12) market risk premium; (13) beta; (14) cost of debt (COD) before tax; and (15) To assess the project value, a reasonable cash-flow model that reflects the profitability impact factors that are the input variables of the DCF method should be established. This paper defines the following 15 profitability impact factors, (1) capital expenditure; (2) material cost; (3) labor cost; (4) net working capital; (5) overhead cost; (6) sale price; (7) production; (8) exchange rate; (9) corporate tax rate; (10) debt-to-equity ratio; (11) risk-free interest rate; (12) market risk premium; (13) it consists of the cost of equity (COE), the COD, the debt-to-capital ratio (DC ratio ), and the corporate tax rate (TAX).…”
Section: Traditional Decision-making Process For the Dcf Modelmentioning
confidence: 99%
See 1 more Smart Citation